2020
DOI: 10.2147/idr.s265292
|View full text |Cite
|
Sign up to set email alerts
|

<p>Estimating the Prevalence and Mortality of Coronavirus Disease 2019 (COVID-19) in the USA, the UK, Russia, and India</p>

Abstract: The aim of this study is to apply the advanced error-trend-seasonal (ETS) framework to forecast the prevalence and mortality series of COVID-19 in the USA, the UK, Russia, and India, and the predictive performance of the ETS framework was compared with the most frequently used autoregressive integrated moving average (ARIMA) model. Materials and Methods: The prevalence and mortality data of COVID-19 in the USA, the UK, Russia, and India between 20 February 2020 and 15 May 2020 were extracted from the WHO websi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Given its attractive applications of the TBATS model, 21 it appeared therefore that this model can be adopted to analyze the HFMD incidence in other countries or regions, even for all the time series, and yet additional work on the current topic is still required to verify its versatility. Additionally, of note, current studies have demonstrated the potential of some new models to perform the long-term forecasting and to handle the nonlinear issue, such as ETS model, 44 long short-term memory neural network (LSTM), 9 and neural network nonlinear autoregression (NNAR) model. 45 Consequently, further investigations into the predictive performance comparison between the TBATS model and the above models are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Given its attractive applications of the TBATS model, 21 it appeared therefore that this model can be adopted to analyze the HFMD incidence in other countries or regions, even for all the time series, and yet additional work on the current topic is still required to verify its versatility. Additionally, of note, current studies have demonstrated the potential of some new models to perform the long-term forecasting and to handle the nonlinear issue, such as ETS model, 44 long short-term memory neural network (LSTM), 9 and neural network nonlinear autoregression (NNAR) model. 45 Consequently, further investigations into the predictive performance comparison between the TBATS model and the above models are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current study, for the first time, focused on the exploration of the utility and adequacy in nowcasting and forecasting the long-term epidemiological trends and seasonality of HFRS, and its predictive accuracy level was compared with the most versatile SARIMA method in the field of time series modeling. 11 , 13 , 16 , 33 It was discovered that the advanced TBATS methods get a more clear perspective of capturing the dynamic dependency structure in the spreading of HFRS over the SARIMA methods in a series of modeling experiments. What’s more, the long-term forecasting results to emerge from the advanced TBATS method remained reliable and robust with the increase of prediction time windows, despite a slight rise in the values of measurement metrics, including MAD, MAPE, RMSE, RMSPE, and MER.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Our recent work suggests that the Error-Trend-Seasonal framework (ETS) technique has many attractive applications in analyzing the long-run temporal behaviors. 33 , 46 Accordingly, we further established the ETS approach based on the HFRS incidence data to nowcast and forecast its epidemics, and the resulting results indicated that the TBATS method is also more useful and robust for describing the long-term trends of HFRS than the ETS technique, except that in 60-step ahead forecast ( Table S8 ). Also, we used the HFRS incidence data in Liaoning province and Shanxi province (which were hit the hardest with HFRS in the past decades in China) to validate the forecasting reliability of TBATS model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the comparations included subsite models, the “best” models specified by iterations had higher possibility to be the real best models. To my knowledge, at least for COVID-19 studies, very few researchers [20] considered subset models (sparse coefficient ARIMA) when they specified their best ARIMA models. With the traditional ARIMA modeling technique, manually specifying lags and model type for the best subsite model is difficult, or sometimes even impossible.…”
Section: Discussionmentioning
confidence: 99%